What Do Illustrators Do? - Christelow, Eileen (New York ClarionBooks, 1999)
Shows two illustrators going through all the steps involved in creating new picture books of "Jack and the Beanstalk," including layout, scale, and point-of-view.
Keywords: Illustration of books; Illustrators